PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI MENULIS TEKS NARASI DI SEKOLAH DASAR - Henny Setiani; Nursifa Maharani; Siti Mulyanti; Muhamad Dansi Marwan; Munawaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning motivation of elementary school students in narrative text writing activities is an issue that needs serious attention from educators. One effort that can be made is to apply the Contextual Teaching and Learning (CTL) learning model, which connects lesson materials to students' real-life experiences. This study aims to examine how the application of the CTL model can enhance the learning motivation of fourth-grade students in narrative text writing. The method used is classroom action research (CAR) with two action cycles. The research subjects were 28 fourth-grade students from an elementary school. Data collection instruments included observation sheets, motivation questionnaires, and writing performance tests. The results showed that the consistent application of the CTL model successfully increased students' learning motivation from the low category in the pre-cycle stage to the high category at the end of Cycle II, with an improvement percentage of 71.4%. In addition, the quality of students' narrative writing also improved significantly. Therefore, the CTL learning model is worthy of being an effective alternative learning strategy to enhance motivation and narrative writing skills in elementary school.